2008
DOI: 10.1093/jae/ejn027
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Grade 12 Pass Rates in the Post-Apartheid South African Schooling System

Abstract: Final Draft"There is no blueprint for a model school that can be reproduced and handed out to policymakers, and such a blueprint is unlikely to be developed in the near future" (Hanushek,1995)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 13 publications
0
27
0
1
Order By: Relevance
“…Thus, the GDP per capita data may be distorted, making it difficult to discern the relationship between income and adventure tourism. Thus, the study went on to examine metropolitan areas by education level as a proxy for likelihood of being employed and having disposable income (Table 2) (Bhorat, Oosthuizen, 2009 When assessed by race, there is almost no relationship between the Indian population and adventure tourism [r = 0.148]. There was a surprisingly strong correlation between the size of the Coloured population and the number of operators [r = 0.637].…”
Section: Results For the Metropolitan Areasmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the GDP per capita data may be distorted, making it difficult to discern the relationship between income and adventure tourism. Thus, the study went on to examine metropolitan areas by education level as a proxy for likelihood of being employed and having disposable income (Table 2) (Bhorat, Oosthuizen, 2009 When assessed by race, there is almost no relationship between the Indian population and adventure tourism [r = 0.148]. There was a surprisingly strong correlation between the size of the Coloured population and the number of operators [r = 0.637].…”
Section: Results For the Metropolitan Areasmentioning
confidence: 99%
“…As for the metropolitan areas, the relationship between adventure tourism and income was explored. Due to the lack of GDP per capita data for these secondary cities, analysis was undertaken by the percentage of the population that had either completed high school or completed a tertiary qualification, as a proxy for income (Bhorat, Oosthuizen, 2009). In that respect it was found there was no relationship between number of operators and percentage of the population who had completed matric [r = 0.0145] or with the number of people who had a tertiary qualification [r = 0.0225].…”
Section: Results For Secondary Citiesmentioning
confidence: 99%
“…Lamdin (1996) found no significant relationship between class size and student success. More recently, Bhorat and Oosthuizen (2009) found that while pupil-teacher ratios and educational resources did not contribute to secondary school pass rates, proxy indicators for teacher characteristics were strong predictors of improvements in African students' performance. Other research on the effects of pupil-teacher ratios in developing areas concludes that pupil-teacher ratio is the most important factor in education production (Ismail & Cheng, 2005;Hungi & Thuku, 2010).…”
Section: Pupil-teacher Ratiomentioning
confidence: 99%
“…Note: assessment based on Fedderke and Luiz, 2002;Fiske and Ladd, 2003;Lee et al, 2005;Moloi, and Strauss, 2005;Oosthuizen and Bhorat, 2006;Gustafsson,2007;Louw et al, 2007;Van der Berg, 2007;Bhorat and Oosthuizen, 2008;Fleisch, 2008;Lam et al, 2008;Van der Berg, 2008;Armstrong, 2009;Chudgar and Kanjee, 2009;Taylor and Yu, 2009;Van der Berg, 2009;Ardington et al, 2011;Frempong et al, 2011;Taylor et al, 2011. …”
Section: Positivementioning
confidence: 99%